Comparison of Pterygium Resection with Conjunctival Auto Graft Versus Amniotic Membrane Graft - Adnan Ahmad, Adnan Alam, Mubashir Rehman, Bilal Khan, Khurshid Alam (Pakistan Journal of Ophthalmology, 2015)
Purpose: To compare the effectiveness of pterygium resection with conjunctival auto graft versus amniotic membrane graft in terms of recurrence rate. Material and Methods: All patients were selected from eye OPD Lady Reading Hospital, Peshawar. Complete slit lamp examination was performed for pterygium. Patients were divided into two groupsi. e Group A who underwent pterygium excision with conjunctival autograft and Group B who underwent pterygium excision with amniotic membrane graft. Follow up was on 3rd month postoperatively at which patient was examined on slit lamp for recurrence of pterygium. Results: The recurrence rate in conjunctival autograft was 10% while the recurrence rate in amniotic membrane graft was 18%. Conjunctival autograft was effective in 90% patients and was not effective in 10% patients, whereas amniotic membrane graft was effective in 82% patients and was not effective in 18% patients. Conclusion: Our study concludes that performing pterygium surgery with amniotic membrane graft compared to conjunctival autograft had a higher recurrence rate. Key words: Primary pterygium, Conjunctiva autograft, Amniotic membrane graft.